The Diversity of Plant as Traditional Culinary Food Wrappers on The Bogor’s Society, West Java Province, Indonesia - Nikmatullah, Muhamad; Rahayu, Mulyati; Kalima, Titi; Setiawan, Marwan; Hasanah, Ida Farida (Al-Kauniyah: Jurnal Biologi, 2024)
AbstractTraditional culinary is a food that has a distinctive taste, commonly consumed by a particular society. Generally, traditional culinary using the diversity of plants to wrap food. The function of plant leaves for food wrapping in consider of natural and safe material. The use of natural materials is very valuable traditional knowledge and includes cultural wealth. The research was conducted to reveal the diversity of plants that are still used as traditional culinary wrapping in Bogor city. This research method used the ethnobotany approach, through observation and direct interview to a key informant up to 20 respondents on the three traditional market’s in Bogor city. The data collection results were produced of 23 types of cuisines in the traditional culinary markets, namely Anyar/Kembang, Sukasari, and Surya Kencana. These traditional culinary are utilized five plant species to wrap food, mostly using banana leaves (Musa spp.) for food packaging of 23 types of the tradisional culinary delights. The advantage of utilizing plants as traditional culinary wrapping infused with flavor to enhance the taste and art. Utilization plants as food wrapping need to preserved, developed, and socialized to public due to its local wisdom environmental sustainability and to reduce the use of non-natural resources that have severe environmental impacts and public health.AbstrakKuliner tradisional merupakan suatu makanan yang mempunyai cita rasa yang khas, biasa dikonsumsi oleh masyarakat tertentu. Umumnya kuliner tradisional memanfaatkan keanekaragaman tumbuhan sebagai pembungkusnya. Penggunaan daun sebagai pembungkus karena bahan alami dan aman untuk membungkus makanan. Penggunaan bahan dari alam adalah pengetahuan tradisional sangat berharga dan termasuk kekayaan budaya. Penelitian tersebut dilakukan untuk mengungkap keanekaragaman tumbuhan yang masih digunakan sebagai pembungkus kuliner tradisional di Kota Bogor. Metode penelitian menggunakan pendekatan etnobotani, melalui observasi dan wawancara langsung kepada informan kunci sebanyak 20 responden di tiga pasar tradisional kota Bogor. Hasil pendataan menunjukkan terdapat 23 jenis kuliner tradisional di pasar Anyar/Kembang, Sukasari, dan Surya Kencana. Kuliner tradisional ini memanfaatkan 5 jenis tumbuhan sebagai pembungkusnya yang sebagian besar adalah daun pisang (Musa spp.) yang digunakan sebagai pembungkus 23 kuliner tradisional. Keuntungan memanfaatkan tumbuhan sebagai pembungkus kuliner tradisional antara lain untuk menambah cita rasa dan seni. Pemanfaatan tumbuhan sebagai pembungkus makanan perlu dilestarikan, dikembangkan, dan disosialisasikan kepada masyarakat umum agar budaya lokal ini senantiasa lestari dan dapat mengurangi pemanfaatan sumber daya non alam yang berdampak buruk terhadap lingkungan dan kesehatan masyarakat.